Stress entropic load: New stress measurement method? - Zlámal, Filip; Lenart, Peter; Kuruczová, Daniela; Kalina, Tomáš; de la Torre, Gabriel; Ramallo, Miguel A; Bienertová-Vašků, Julie (PLoS One, 2018)
While stress is a widely utilized concept, no direct methods facilitating its measurement are currently available. In our previous work we proposed stress entropic load (SEL) as a potential new marker of stress response in the human body. However, at that time no method for SEL measurement existed. In this pilot study we devised and then tested methodology for SEL measurement. Healthy male participants were monitored by indirect calorimetry and thermography while resting and subsequently while under prolonged mental effort. The acquired data was then used to calculate the temporal development of SEL for each participant. Our results show that SEL production increased significantly in participants subjected to prolonged mental effort. Furthermore, we observed that the calculated development of SEL over time may be used to accurately determine the time point at which participants started performing stressful tasks.
Keywords: dospělí; biologické modely; Healthy Volunteers; Neuropsychological Tests; Adult; mladý dospělý; psychický stres; zdraví dobrovolníci pro lékařské studie; neuropsychologické testy; termografie; lidé; Models, Biological; Pilot Projects; pilotní projekty; entropie; Calorimetry, Indirect; Male; Stress, Psychological; Young Adult; mužské pohlaví; Thermography; nepřímá kalorimetrie; Entropy; Humans